PENGARUH BEBAN KERJA, STRES DAN DISIPLIN TERHADAP PRESTASI KERJA GURU PADA SMA NEGERI WILAYAH BARAT KABUPATEN BIREUEN - Herlita; Fauzi, Fauzi (LPPM-UNIKI, 2022)
This study aims to explore further and provide empirical information about the effect of workload, work stress and work discipline on teacher work performance at SMAN West Region Bireuen Regency. The results of the path analysis show, 1) There is a direct and indirect effect of workload on the work performance of the teachers of the West Region State Senior High School, Bireuen Regency, which is 19.54%. 2) There is a direct and indirect effect of work stress on the work performance of the teachers of the West Region State Senior High School, Bireuen Regency, which is 18.39%. 3) There is a direct and indirect effect of work discipline on the work performance of the teachers of the West Region State Senior High School, Bireuen Regency, which is 19.34%. 4) Simultaneously, the variables of workload, work stress and work discipline have an effect on the work performance of the teachers of the West Region Senior High School, Bireuen Regency. This result is evidenced by the results of the F test obtained that Fcount is 46.928 while the Ftable value for the number of respondents is 170 people at a significance level (α) = 5%, which is 2.27. This shows that Fcount > Ftable with a significance level of 0.05. 5) The value of the coefficient of determination of 0.434 explains that the contribution of workload, work stress and work discipline to the work performance of the teachers of the West Region Public High School, Bireuen Regency is 43.4%. While the rest (residual value) of the role of the variables that were not studied was 56.6%. The residual value shows that there are other factors that can affect the teacher's performance variables, organizational culture, work environment, facilities and infrastructure and others.